Gender-wise Study of Family Climate for Adolescents in Urban India. Issue 2 (December 2019) - Mishra, Santwana G.
In this study, the researcher has studied the family climate for adolescents in urban society in India. The typical urban family in India has modern lifestyle and is also technologically advanced. It is believed that these families are progressive in comparison to their rural counterparts. The present research work is aimed to study the family climate of adolescents from urban families in association with their gender. A total of 309 adolescents (163 boys and 146 girls) in the age group of 14–15 years were randomly selected from the secondary schools of Aurangabad, a city in Maharashtra state of India for the academic year 2016–2017. The tool used for data collection was family climate scale (FCS) developed by Dr Beena Shah and published by National Psychological Corporation, Agra, India. In this test, family climate means an interpersonal relationship between the parents and the child. The test assesses the family climate on 10 dimensions. Data were collected by personally meeting the adolescents. The collected data were analysed using chi-squared test. The study showed that more male adolescents had favourable family climate as compared to female adolescents and the difference was significant. Also, the number of female adolescents having unfavourable family climate was significantly higher as compared to male adolescents. The study concluded that the age-old gender bias is still very much prevalent in India. The boys are favoured and given a more conducive and positive family atmosphere as compared to the girls. Hence, there is a need for creating awareness to curb this bias and help the girls in the family to be treated at par with their male counterparts.